Phosphate restriction impairs mTORC1 signaling leading to increased bone marrow adipose tissue and decreased bone in growing mice - Ko, Frank C.; Kobelski, Margaret M.; Zhang, Wanlin; Grenga, Gina M.; Martins, Janaina S.; Demay, Marie B. (Journal of bone and mineral research, 2021)
ABSTRACT Bone marrow stromal cells (BMSCs) are multipotent cells that differentiate into cells of the osteogenic and adipogenic lineage. A striking inverse relationship between bone marrow adipose tissue (BMAT) and bone volume is seen in several conditions, suggesting that differentiation of BMSCs into bone marrow adipocytes diverts cells from the osteogenic lineage, thereby compromising the structural and mechanical properties of bone. Phosphate restriction of growing mice acutely decreases bone formation, blocks osteoblast differentiation and increases BMAT. Studies performed to evaluate the cellular and molecular basis for the effects of acute phosphate restriction demonstrate that it acutely increases 5′ adenosine monophosphate–activated protein kinase (AMPK) phosphorylation and inhibits mammalian target of rapamycin complex 1 (mTORC1) signaling in osteoblasts. This is accompanied by decreased expression of Wnt10b in BMSCs. Phosphate restriction also promotes expression of the key adipogenic transcription factors, peroxisome proliferator–activated receptor γ (PPARγ) and CCAAT‐enhancer binding protein α (CEBPα), in CXCL12 abundant reticular (CAR) cells, which represent undifferentiated BMSCs and are the main source of BMAT and osteoblasts in the adult murine skeleton. Consistent with this, lineage tracing studies reveal that the BMAT observed in phosphate‐restricted mice is of CAR cell origin. To determine whether circumventing the decrease in mTORC1 signaling in maturing osteoblasts attenuates the osteoblast and BMAT phenotype, phosphate‐restricted mice with OSX‐CreERT2–mediated haploinsufficiency of the mTORC1 inhibitor, TSC2, were generated. TSC2 haploinsufficiency in preosteoblasts/osteoblasts normalized bone volume and osteoblast number in phosphate‐restricted mice and attenuated the increase in BMAT observed. Thus, acute phosphate restriction leads to decreased bone and increases BMAT by impairing mTORC1 signaling in osterix‐expressing cells. © 2021 American Society for Bone and Mineral Research (ASBMR).